LEARNING TOOLS WITH INQUIRY MODELS INTEGRATED OF CHARACTER EDUCATION - Azmi, Irham; Jufri, A. Wahab; Makhrus, Muh. (Lensa: Jurnal Kependidikan Fisika, 2020)
This study aimed to describe the characteristics and validity of learning tools with inquiry models integrated of character education that is used in learning at junior high school level. The intended learning tools include syllabus, lesson plans, teaching materials, student worksheets, and scientific creativity test instruments. This research is an evaluative descriptive study that describes the characteristics and evaluates the quality of the validity of learning tools. The learning tools validation process involves three validators who validate the learning tools on aspects of content validity and construct validity. The validation results show that the validator's assessment of the learning framework developed in the aspects of content validity and construct validity are categorized as very valid with an average range of scores of ?85%, with a percentage of agreement ?75%. The results of this study can be used as a foundation that the learning tools with inquiry models integrated of character education can be implemented in the field.